2019
DOI: 10.5993/ajhb.43.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Treatment Needs of Low SES Cervical Cancer Survivors

Abstract: Objectives: We investigated the treatment needs and preferences of low socioeconomic status cervical cancer survivors to inform the adaptation of a theoretically- and empirically-based Motivation and Problem-Solving approach to facilitate cessation in this at-risk population. Methods: Individual in-depth interviews were conducted with 12 female smokers with cervical cancer. Interviews were audio-recorded, transcribed, and analyzed using NVivo 10. Results: Most participants did not believe that smoking caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 55 publications
(60 reference statements)
1
18
0
Order By: Relevance
“…More than three-quarters of this sample reported smoking in the past month. Participants’ average number of cigarettes per day and time to first cigarette both indicate moderate nicotine dependence, consistent with prior, similar studies (Hoover et al, 2019; Waggoner et al, 2010). Furthermore, one-quarter of current smokers reported noncigarette tobacco use in the past month, which means dual and poly tobacco use may well occur in CCS.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…More than three-quarters of this sample reported smoking in the past month. Participants’ average number of cigarettes per day and time to first cigarette both indicate moderate nicotine dependence, consistent with prior, similar studies (Hoover et al, 2019; Waggoner et al, 2010). Furthermore, one-quarter of current smokers reported noncigarette tobacco use in the past month, which means dual and poly tobacco use may well occur in CCS.…”
Section: Discussionsupporting
confidence: 85%
“…Albeit a very small literature (Hoover et al, 2019; Iyer et al, 2016; Schlumbrecht et al, 2014; Waggoner et al, 2010), there are some important findings from prior studies of CCS’ smoking. Like most smokers who eventually develop a smoking-related health problem, CCS who smoke report a long history of smoking and high nicotine dependence (Hoover et al, 2019; Waggoner et al, 2010). To date, only one study has examined demographic, clinical, or psychosocial correlates of smoking after cervical cancer diagnosis (Waggoner et al, 2010), and with so little data to consider, no firm conclusions can be made.…”
mentioning
confidence: 99%
“…In-depth interview participants also indicated that it would be important to address stress, issues specific to cervical cancer survivorship, and lifestyle factors such as physical activity and healthy eating. Finally, they emphasized the importance of including NRT as part of the intervention [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, participants' responses could be interpreted as self‐protection in combination with limited knowledge about the causal role of smoking in cervical cancer. In another study with CCS who smoked, individuals were similarly unaware or skeptical of the causal role of smoking instead emphasizing HPV's contributions , which highlights the need to better educate the general public specifically about the myriad causes of cervical cancer and the numerous cancers now linked to smoking. In general, cancer survivors express a great diversity of opinion about what causes cancer, citing biological (e.g., family history), lifestyle (e.g., sun protection), environmental (e.g., pollution, occupational hazards), and existential/experiential (e.g., God, stress) factors , only some of which have strong empirical support.…”
Section: Discussionmentioning
confidence: 99%